2021
DOI: 10.1021/acs.langmuir.1c00198
|View full text |Cite
|
Sign up to set email alerts
|

Yolk-Shelled Gold@Cuprous Oxide Nanostructures with Hot Carriers Boosting Photocatalytic Performance

Abstract: Plasmonic Au nanoparticles (NPs) have been commonly used to enhance the photocatalytic activity of Cu2O. Till now, core–shell Au NP@Cu2O composites have been reported in previous studies. Yet, these Au@Cu2O composites only exhibit visible light response. Other special Au nanostructures, such as Au nanorods (NRs) or Au nanobipyramids (NBPs), which possess near-infrared light absorption, were rarely used to endow the near-infrared light response for Cu2O. In this work, for the first time, we used Au NPs, Au NRs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The metal-semiconductor nonradiative decay can improve electron transformation and prevent electron-hole pair recombination. [28][29][30] Previous studies have shown several Au nanostructures combined with Cu 2 O particles for various photochemical and electrochemical reactions, for example, the photocatalytic destruction, 26 hydrogen evolution reaction, 31 oxygen evolution reaction, 32 CO oxidation, 33 CO 2 RR but with Cu 2 O nanotubes with Au NP deposition, 34 instead of the direct deposition of thin lms in the current study, which is arguably easier to prepare and replicate for future development.…”
Section: Introductionmentioning
confidence: 73%
“…The metal-semiconductor nonradiative decay can improve electron transformation and prevent electron-hole pair recombination. [28][29][30] Previous studies have shown several Au nanostructures combined with Cu 2 O particles for various photochemical and electrochemical reactions, for example, the photocatalytic destruction, 26 hydrogen evolution reaction, 31 oxygen evolution reaction, 32 CO oxidation, 33 CO 2 RR but with Cu 2 O nanotubes with Au NP deposition, 34 instead of the direct deposition of thin lms in the current study, which is arguably easier to prepare and replicate for future development.…”
Section: Introductionmentioning
confidence: 73%
“…In our previous work, we have already proved that yolk–shelled Au@Cu 2 O could be obtained with this Ostwald ripening process and exhibit much better photocatalytic activities than solid Au@Cu 2 O. 16 Accordingly, in this work, y-Au@Cu 2 O/rGO must be preferred rather than the solid core–shelled Au@Cu 2 O/rGO.…”
Section: Resultsmentioning
confidence: 99%
“…14 Recently, our group has reported jujube-like Au NBP@Cu 2 O core-shelled composites and yolkshelled Au NR/NBP@Cu 2 O composites, respectively, revealing these Au and Cu 2 O composites possessed strong light absorption in the near-infrared region as well as full-spectrum-driven photocatalytic performance. 15,16 The stability of Cu 2 O was also improved obviously due to the quick transfer of photogenerated holes to Au. Although the above Au NR/NBPs and Cu 2 O composite photocatalysts showed considerable photocatalytic behaviour, there still existed a common problem that the photogenerated carriers on Cu 2 O and hot carriers on Au are limited to some degree in the core-shelled structure that needed to be adequately transferred and separated in order to further boost the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Core–shell nanoparticles have attracted much attention due to their functional core and protective shell (high specific surface area and modified surface). As a special kind of core–shell structure, the yolk–shell structure has a movable core and a hollow nanocavity shell, and its composite function is expected to be further improved and applied. , Different kinds of yolk–shell nanoparticles have been developed and applied in various fields, such as catalysis, energy storage, , biological imaging, and drug delivery carriers. However, it remains to be further studied to simplify and optimize the preparation process of yolk–shell nanoparticles.…”
Section: Introductionmentioning
confidence: 99%